The Utilization of Twitter in The Anticipation of Covid-19 Hoax News in Yogyakarta City - Ohorella, Noviawan Rasyid (COMMUSTY Journal of Communication Studies and Society, 2023)
The contemporary era of openness has exerted a significant influence on social media platforms, particularly Twitter. This is mostly due to the platform's ability to facilitate the expression of opinions and the rapid dissemination of news by individuals. The act of expressing opinions necessitates the inclusion of the need to substantiate the validity of the information being conveyed. Data-driven information can be substantiated and expressed. During the ongoing Covid-19 pandemic, a substantial amount of information pertaining to the coronavirus remains ambiguous or has yet to be definitively established. The prevalence of misinformation is on the rise due to individuals' acceptance and dissemination of false information without conducting thorough research to ascertain its veracity. Consequently, the dissemination of false coronavirus information on social media, particularly Twitter, has occurred.